Preparation method of high-strength, high-elasticity and fatigue-resistant copper-niobium composite plate strip

Through winding composite-extrusion-pull, cluster composite-extrusion-pull deformation and heat treatment-rolling deformation processes, nanoscale copper-niobium composite plate strips are formed, which solves the poor performance of existing copper-based alloys at high temperatures. The problem is that high strength, high conductivity and fatigue resistance are achieved, and the process is safe and easy to industrially produce.

CN119188173AActive Publication Date: 2024-12-27NORTHWEST INSTITUTE FOR NONFERROUS METAL RESEARCH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411315436.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2024-12-27
Estimated Expiration
2044-09-20

AI Technical Summary

Technical Problem

The existing copper-based elastic alloys have poor thermal stability and insufficient stress relaxation resistance when used at high temperatures, and the preparation process is complex and unsafe, making it difficult to have high strength, high conductivity, fatigue resistance and high temperature stress resistance.

Method used

Using winding composite-extrusion-pull, cluster composite-extrusion-pull deformation and heat treatment-rolling deformation processes, copper-niobium composite plate strips with nanoscale copper and niobium biphasic layer structures are formed, and copper alloys and niobium are used. The ternary composite structure guides nano-effects, gradient effects and interface effects, improves the yield strength and tensile strength of copper-niobium composite plate strips, and achieves high conductivity and fatigue resistance.

Benefits of technology

The copper-niobium composite plate belt has high yield strength, tensile strength, elasticity, conductivity and fatigue resistance. It has a softening temperature of up to 600℃. It has a simple process and a safe material, making it suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119188173A_ABST
    Figure CN119188173A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-strength, high-elasticity and fatigue-resistant copper-niobium composite plate strip, which comprises the following steps of: 1, winding and forming a copper foil and a niobium foil, placing the copper foil and the niobium foil in a copper alloy sheath for hot extrusion deformation, and performing multi-pass cold drawing and intermediate annealing to obtain a copper-niobium composite wire; 2, bundling and assembling the copper-niobium composite wires, placing the copper-niobium composite wires in a copper alloy sheath for hot extrusion deformation, and obtaining a copper alloy / copper / niobium structure composite round wire through multi-pass cold drawing and twice intermediate annealing; and thirdly, the copper alloy / copper / niobium structure composite round wire is subjected to heat treatment and then subjected to multi-pass cold rolling deformation. According to the preparation method, the copper-niobium composite plate strip of which the surface layer is a micron-scale copper alloy layer and the interior is of a nano-scale copper and niobium double-phase laminated structure which is alternately distributed is obtained through winding compounding, extruding, drawing, bundling compounding, extruding, drawing deformation and heat treatment and rolling deformation, so that the strength of the copper-niobium composite plate strip is improved; the composite material has the advantages of high rebound resilience, high conductivity, fatigue resistance, stress relaxation resistance, thermal stability and high wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of high-strength and high-elasticity alloys, and specifically relates to a method for preparing a high-strength, high-elasticity, fatigue-resistant copper-niobium composite plate strip. Background Art

[0002] Copper-based elastic alloys are widely used in medical, aerospace and navigation instruments, machinery manufacturing, electronic power and instrument manufacturing. They are mainly used to produce various current-carrying elastic components, contact springs, switches, converters, terminal components, etc., which require them to have high resilience, high mechanical strength, high electrical conductivity, excellent fatigue resistance and high-temperature thermal stability. At present, the copper-based elastic alloys on the domestic market are mainly beryllium bronze and tin-phosphor bronze. However, the beryllium powder used in the preparation of beryllium bronze materials is highly toxic. At the same time, the beryllium bronze strips currently produced in China have serious grain boundary segregation problems, poor thermal stability, poor high-temperature stress relaxation resistance, and are not suitable for long-term use at high temperatures. The preparation process of tin-phosphor bronze is complicated, the processability is poor, the casting process is prone to reverse segregation, it is easy to crack during cold rolling, and its conductivity is relatively low.

[0003] A large number of academic studies and customer feedback indicate that beryllium bronze and tin-phosphor bronze are currently used as the main materials for manufacturing elastic electrical components. When used as conductive high-temperature stress-bearing connectors (such as electrodes for contact welding machines), their performance deteriorates significantly as the service time increases. In order to improve the thermal stability and stress relaxation resistance of elastic copper-based alloys, people have developed Cu-Ni-Sn alloy plates. However, the addition of multiple alloying elements, the addition of additional atoms or the presence of precipitation phases during the formation of saturated solid solutions and aging precipitation greatly weaken the electrical conductivity of Cu-Ni-Sn alloy plates. Therefore, it is an important issue to design new copper-based composite material structures and components, propose new processing and forming processes, and develop new copper-based composite plates, so that the prepared copper-based composite plates can achieve high strength, high conductivity, high thermal stability, excellent fatigue resistance and high-temperature stress relaxation resistance at the same time. It is of great significance to replace the existing elastic copper-based alloy plates and solve the problem of poor high-temperature service performance. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a method for preparing a high-strength, high-elastic, fatigue-resistant copper-niobium composite plate and strip in view of the deficiencies of the above-mentioned prior art. The method obtains a copper-niobium composite plate and strip with a core wire surface layer of a micrometer-scale copper alloy layer and an alternatingly distributed nanoscale copper and niobium dual-phase sheet structure through winding composite-extrusion-drawing, cluster composite-extrusion-drawing deformation, and heat treatment-rolling deformation. The method uses a ternary composite structure of copper alloy, copper and niobium to induce nano effect, gradient effect, and interface effect to act on the copper-niobium composite plate and strip, thereby improving the yield strength and tensile strength of the copper-niobium composite plate and strip, achieving high resilience of the copper-niobium composite plate and strip, and making the copper-niobium composite plate and strip have high electrical conductivity, fatigue resistance, stress relaxation resistance, thermal stability, and high wear resistance, solving the problem that the existing copper-based alloy cannot have high strength, high elasticity, excellent electrical conductivity, fatigue resistance, thermal stability, and high wear resistance.

[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a high-strength, high-elastic and fatigue-resistant copper-niobium composite plate and strip, characterized in that the method comprises the following steps:

[0006] Step 1: using an automatic foil winding device to alternately wind a micron-level high-purity copper foil and a high-purity niobium foil in a layered distribution according to a volume ratio of 1:1, and then placing them in a copper alloy sheath to obtain a copper-niobium wound foil composite sheath, and then vacuum-sealing and welding the two ends of the copper-niobium wound foil composite sheath and then performing hot extrusion deformation to make the interface of the high-purity copper foil and the high-purity niobium foil solid-state welded to obtain a copper-niobium composite rod with a winding structure, and then performing multiple cold drawing and intermediate annealing on the copper-niobium composite rod with a winding structure to obtain a copper-niobium composite wire with a hexagonal cross-section;

[0007] Step 2: The copper-niobium composite wire with a hexagonal cross-section obtained in step 1 is used as a core wire for bundling and assembly and placed in a copper alloy sheath to obtain a copper-niobium bundled composite sheath, and then the two ends of the copper-niobium bundled composite sheath are vacuum-sealed and then hot-extruded to deform, so that the outer copper alloy interface of the inner core wire is solid-state welded, and the outer sheath copper alloy is solid-state welded with the outer copper alloy interface of the contacting core wire, so as to obtain a copper-niobium bundled composite rod with a multi-core bundled structure, and then the copper-niobium bundled composite rod with a multi-core bundled structure is subjected to multi-pass cold drawing, two intermediate annealings, and multi-pass cold drawing to obtain a copper alloy / copper / niobium structure composite round wire with an outer copper alloy layer and an inner copper-niobium core wire;

[0008] Step 3: heat-treating the copper alloy / copper / niobium structure composite round wire obtained in step 3, and then performing multiple cold rolling deformation to obtain a high-strength, high-elastic, fatigue-resistant, wear-resistant, and thermally stable copper-niobium composite strip; the copper-niobium composite strip has a tensile strength σb ≥ 1000 MPa, a yield strength / elastic modulus of 0.008 or more, and a cyclic loading number N ≥ 1.7×10 6The softening temperature is above 600°C and the electrical conductivity is above 65% IACS.

[0009] The present invention forms a copper-niobium wound foil material by stacking and winding a high-purity copper foil and a high-purity niobium foil, and puts the foil material into a copper alloy sheath, and obtains a copper-niobium composite wire material with a hexagonal cross-section through degassing, sealing welding, hot extrusion deformation, cold drawing deformation and intermediate annealing heat treatment, and then the copper-niobium composite wire material is assembled as a core wire and placed in a copper alloy sheath, and then degassing, sealing welding, hot extrusion deformation, cold drawing plate deformation and intermediate annealing heat treatment are performed to obtain a copper alloy / copper / niobium structure composite round wire, and then the copper-niobium composite plate and strip are obtained by annealing heat treatment and cold rolling deformation. In the above-mentioned preparation process, the present invention obtains a copper-niobium composite strip with an alternatingly distributed nanoscale copper and niobium dual-phase sheet structure through winding composite-extrusion-drawing, cluster composite-extrusion-drawing deformation, and heat treatment-rolling deformation. The nanoscale copper-niobium core wire and the high-density copper / niobium interface layer introduce a large amount of gradient stress / strain and geometric necessary dislocation at the copper / niobium interface, which greatly reduces the elastic modulus of the copper-niobium composite strip. The elastic modulus value is 40GPa to 60GPa lower than the elastic modulus of the copper alloy, thereby improving the yield strength and tensile strength (>900MPa) of the copper-niobium composite strip, and achieving high resilience of the copper-niobium composite strip. At the same time, the present invention The large plastic deformation of the bundle drawing makes the copper and niobium sheet structure a fiber layer with a strong texture orientation, forming a fiber structure similar to a single crystal structure, ensuring that the copper-niobium composite plate and strip obtain a higher conductivity (≥65% IACS), and the nano-core wire structure, the fiber structure similar to the single crystal and the high-density copper / niobium interface layer also greatly improve the fatigue resistance and stress relaxation resistance of the copper-niobium composite plate and strip, so that it has good thermal stability (softening temperature ≥600°C); in addition, the copper alloy sheath used in both the primary assembly sheath and the secondary composite sheath of the present invention has good wear resistance and stress relaxation resistance, thereby achieving high wear resistance of the copper-niobium composite plate and strip.

[0010] The above-mentioned method for preparing a high-strength, high-elastic, fatigue-resistant copper-niobium composite strip is characterized in that the mass purity of the high-purity copper foil and the high-purity niobium foil in step 1 are both 99.9%, and the thickness is the same, the thickness range is 150μm to 500μm, and the outer diameter of the copper alloy sheath is 80mm to 120mm. The present invention controls the thickness of the high-purity copper foil and the high-purity niobium foil, the outer diameter of the copper alloy sheath, and regulates the copper / niobium interface density, the copper and niobium core wire dimensions, and the mass ratio of copper, thereby controlling the internal gradient stress / strain level, dislocation movement and the critical shear stress and electrical transport capacity of the transmission, so that the prepared copper-niobium composite strip obtains the best strength, conductivity, high-temperature thermal stability, and fatigue resistance matching.

[0011] The above-mentioned method for preparing a high-strength, high-elasticity, fatigue-resistant copper-niobium composite plate and strip is characterized in that the deformation rate of the multiple cold drawing passes in step one is 10% to 15%, the temperature of the intermediate annealing is 680°C to 720°C, and the time is 2.5h to 3h.

[0012] The above-mentioned method for preparing a high-strength, high-elasticity, fatigue-resistant copper-niobium composite plate and strip is characterized in that the copper alloy sheath in step 2 is copper-nickel-silicon or copper-nickel-tin alloy, with an outer diameter of 80mm to 150mm, and the temperature of the hot extrusion deformation is 700°C to 750°C; the deformation rate of the multi-pass cold drawing is 10% to 15%, and the intermediate annealing temperature is 680°C to 720°C; the copper alloy / copper / niobium structure composite round wire is an outer layer of high-strength, wear-resistant copper alloy coated with an internal high-strength, high-elasticity, high-toughness, high thermal stability and fatigue resistance copper-niobium nano-composite core wire. The present invention selects wear-resistant copper-nickel-silicon or copper-nickel-tin alloy as an outer sheath so that the copper-niobium composite plate and strip has high wear resistance, and controls the size of the copper alloy sheath to obtain a copper-niobium composite plate and strip with different wear-resistant layer thicknesses; at the same time, by designing a copper alloy / copper / niobium structure composite round wire with an outer layer of copper alloy and an internal copper / niobium nano-composite core wire structure, the copper-niobium composite plate and strip has high strength and wear resistance on the outside, and high strength, high elasticity, high toughness, high thermal stability and fatigue resistance on the inside.

[0013] The above-mentioned method for preparing a high-strength, high-elastic, fatigue-resistant copper-niobium composite strip is characterized in that the diameter of the copper alloy / copper / niobium structure composite round wire in step three is φ3.5mm~φ5.0mm; the temperature of the heat treatment is 650℃~700℃, and the holding time is 2h~3h; the pass deformation rates of the multiple cold rolling deformations are respectively: when the thickness of the cold rolling object strip is 1mm or more, it is 25%~40%, when the thickness of the cold rolling object is 0.5mm or more and less than 1mm, it is 15%~20%, when the thickness of the cold rolling object is 0.3mm or more and less than 0.5mm, it is 5%~15%, when the thickness of the cold rolling object is less than 0.3mm, it is 1%~5%; the thickness of the copper-niobium composite strip is 0.25mm~0.5mm. The present invention optimizes its subsequent uniform plastic deformation ability by controlling the size and heat treatment process of the copper alloy / copper / niobium structure composite round wire, and realizes the copper-niobium composite strip with excellent performance and thin size without intermediate annealing.

[0014] Compared with the prior art, the present invention has the following advantages:

[0015] 1. The present invention obtains a copper-niobium composite strip with an alternatingly distributed nanoscale copper and niobium dual-phase sheet structure through a winding composite-extrusion-drawing, a cluster composite-extrusion-drawing deformation, and a heat treatment-rolling deformation process. The nanoscale copper-niobium core wire and the high-density copper / niobium interface layer introduce a large amount of gradient stress / strain and geometric necessary dislocation at the copper / niobium interface, which greatly reduces the elastic modulus of the copper-niobium composite strip, improves the yield strength and tensile strength of the copper-niobium composite strip, and achieves high resilience of the copper-niobium composite strip. At the same time, the cluster drawing large plastic deformation forms a fiber structure similar to a single crystal structure, ensuring that the copper-niobium composite strip obtains higher conductivity and fatigue resistance, stress relaxation resistance, and thermal stability, and the copper alloy sheath used achieves high wear resistance of the copper-niobium composite strip.

[0016] 2. Compared with the elastic beryllium bronze alloy, the preparation process needs to add highly toxic and flammable beryllium powder, and the beryllium powder is easy to volatilize during the addition process, which requires strict sealing during the preparation process and strict protection of operators, thus causing production inconvenience and safety hazards. The materials used in the preparation method of the present invention include high-purity copper foil, high-purity niobium foil, oxygen-free copper and copper alloy sheath, which are non-toxic, have good stability, and are easy to obtain and store. The materials and the preparation process are safe and easy to operate.

[0017] 3. The large plastic deformation process flow of the present invention, such as winding composite-extrusion-drawing, bundle composite-extrusion-drawing deformation, heat treatment-rolling deformation, etc., is simple and easy to realize industrial mass production; at the same time, by stacking and winding high-purity copper foil and high-purity niobium foil and bundling and assembling copper-niobium composite wires and then performing large plastic deformation, it is easy to achieve the uniformity of the internal structure of the copper-niobium composite plate and strip and obtain nanoscale core wires, which solves the problems of organizational segregation, uneven reinforcement phase size and uneven composition in the current elastic copper-based alloy materials beryllium bronze, tin-phosphor bronze and copper-nickel-tin alloy in the preparation process using smelting and powder metallurgy methods, and ensures the uniformity of the mechanical properties of the high-strength and high-elastic copper-niobium composite plate and strip.

[0018] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a physical picture of the copper alloy / copper / niobium structure composite round wire prepared in Examples 1 to 3 of the present invention.

[0020] Figure 2 This is a physical picture of the copper-niobium composite strip prepared in Examples 1 to 3 of the present invention.

[0021] Figure 3 This is a graph showing the results of electron backscattered pattern (EBSD) analysis of the longitudinal section of the copper-niobium composite plate prepared in Example 1 of the present invention.

[0022] Figure 4 This is a SEM image of the copper-niobium nanocore wires in the copper-niobium composite strip prepared in Example 1 of the present invention.

[0023] Figure 5 This is a TEM image of the nano-niobium core wire in the copper-niobium composite plate and strip prepared in Example 1 of the present invention.

[0024] Figure 6 This is a NS curve diagram of the bending fatigue test of the copper-niobium composite strip prepared in Example 1 of the present invention.

[0025] Figure 7 This is a comparison chart of the springback analysis of the copper-niobium composite strips prepared in Examples 1 to 3 of the present invention and the beryllium-nickel-copper alloy strips. DETAILED DESCRIPTION

[0026] Example 1

[0027] This embodiment includes the following steps:

[0028] Step 1: using an automatic foil winding device, alternately stacking high-purity copper foil and high-purity niobium foil with a mass purity of 99.9% and a thickness of 150 μm in a layered distribution according to a volume ratio of 1:1, and winding them on an automatic winding device, and then placing them in a copper alloy sheath with an outer diameter of 80 mm and a wall thickness of 8 mm to obtain a copper-niobium wound foil composite sheath, and then vacuum degassing the copper-niobium wound foil composite sheath, and then electron beam sealing welding at both ends, and hot extrusion deformation at 700° C., so that the interface of the high-purity copper foil and the high-purity niobium foil is solid-state welded, and a copper-niobium composite rod with a diameter of Φ20 mm and a winding structure is obtained, and then the copper-niobium composite rod with a winding structure is subjected to multi-pass cold drawing with a pass deformation rate of 10% and intermediate annealing at 720° C. for 3 hours to obtain a copper-niobium composite wire with a hexagonal cross-section;

[0029] Step 2: Bundle and assemble 853 copper-niobium composite wires with a hexagonal cross-section obtained in step 1 as core wires and place them in a copper-nickel-silicon alloy sheath with an outer diameter of 80 mm to obtain a copper-niobium bundled composite sheath. Then, vacuum seal and weld both ends of the copper-niobium bundled composite sheath and perform hot extrusion deformation at 750°C to solid-state weld the outer copper alloy interface of the inner core wire, and solid-state weld the outer copper alloy interface of the outer sheath with the outer copper alloy of the contacting core wire to obtain a copper-niobium bundled composite rod with a diameter of 20 mm and a multi-core bundled structure. Then, the copper-niobium bundled composite rod with a multi-core bundled structure is subjected to multi-pass cold drawing with a pass deformation rate of 15%, two intermediate annealings at 720°C for 3 hours, and multi-pass cold drawing with a pass deformation rate of 15% to obtain a copper alloy / copper / niobium structure composite round wire with a diameter of φ5.0 mm, an outer layer of high-strength and wear-resistant copper alloy sheathing an internal high-strength, high-elasticity, high-toughness, high thermal stability and fatigue resistance copper-niobium nanocomposite core wire, such as Figure 1 As shown;

[0030] Step 3: The copper alloy / copper / niobium structure composite round wire with a diameter of φ5.0 mm obtained in step 3 is subjected to a heat treatment at 700°C for 2 hours, and then subjected to multiple cold rolling deformation, wherein the pass deformation rates of the multiple cold rolling deformation are: 40% when the thickness of the cold rolled object strip is 1 mm or more, 20% when the thickness of the cold rolled object strip is 0.5 mm or more and less than 1 mm, 15% when the thickness of the cold rolled object strip is 0.3 mm or more and less than 0.5 mm, and 50% when the thickness of the cold rolled object strip is less than 0.3 mm. %, and the diameter of the copper alloy / copper / niobium structure composite round wire changes to 5mm, 4.4mm, 3.71mm, 3.5mm, 2.98mm, 2.53mm, 2.21mm, 1.89mm, 1.61mm, 1.32mm, 1.07mm, 0.89mm, 0.71mm, 0.55mm, and 0.5mm in the process of multiple cold rolling deformation, and finally a high-strength, high-elastic, fatigue-resistant, wear-resistant, and thermally stable copper-niobium composite strip with a thickness of 0.5mm is obtained. Figure 2 shown.

[0031] The strength and elastic modulus of the copper-niobium composite strip prepared in this embodiment and the beryllium-nickel-copper alloy strip with the grade C17510 in the prior art (alloy element composition is Be 0.2%-0.6%, Ni 1.4%-2.2%, and the rest is Cu) were tested, and the results are shown in Table 1 below.

[0032] Table 1

[0033]

[0034] It can be seen from Table 1 that the yield strength σ0.2 and tensile strength σb of the copper-niobium composite strip prepared in this embodiment are higher than the yield strength σ0.2 and tensile strength σb of the beryllium-nickel-copper alloy strip, wherein, at different temperatures (20°C to 300°C), the tensile strength σb of the copper-niobium composite strip is about 150MPa higher than that of the beryllium-nickel-copper alloy strip, and the yield strength σ0.2 of the copper-niobium composite strip is about 15MPa higher than that of the beryllium-nickel-copper alloy strip; at the same time, the elastic modulus E0 of the copper-niobium composite strip prepared in this embodiment is lower than that of the beryllium-nickel-copper alloy strip, and its elastic modulus is about 30GPa to 40GPa smaller than that of the beryllium-nickel-copper alloy strip at different deformation temperatures (20°C to 300°C). Finally, the ratio of the yield strength to the elastic modulus of the copper-niobium composite strip is 30% to 40% higher than that of the beryllium-nickel-copper alloy strip, which indicates that the copper-niobium composite strip has better resilience.

[0035] The bending fatigue properties of the copper-niobium composite strip prepared in this embodiment were tested, and three samples were selected. The results are shown in Table 2 below.

[0036] Table 2

[0037] Sample No. Peak load(N) Stress level (%) Number of cycles (circles) Test results 1 753.75 75 22638 fracture 2 502.5 50 177402 fracture 3 301.5 30 1731494 fracture

[0038] It can be seen from Table 2 that the number of fatigue cycles that the fracture circle of the copper-niobium composite strip prepared in this embodiment can withstand under a peak load of 30% is 1.7×10 6 Its fatigue performance is close to that of pure copper (the number of cycles before fracture is 5×10 7 times), and is much higher than the fatigue performance of beryllium bronze (the number of cycles before fracture is 2×10 4 times), indicating that the copper-niobium composite strip prepared by the present invention has very excellent fatigue performance.

[0039] The electrical conductivity of the copper-niobium composite strip prepared in this embodiment was tested and compared with the electrical conductivity of the annealed C17510 beryllium-nickel-copper alloy strip. The results are shown in Table 3 below.

[0040] Table 3

[0041] Conductivity Copper-niobium composite strip in Example 1 67.12% C17510 Beryllium Nickel Copper Alloy Strip 51.96%

[0042] It can be seen from Table 3 that the electrical conductivity of the copper-niobium composite strip prepared in this embodiment is higher than that of the beryllium-nickel-copper alloy strip, indicating that its internal nanoscale strongly oriented core wire structure ensures its high strength and high electrical conductivity.

[0043] Figure 3 This is the electron backscattered pattern (EBSD) analysis result of the longitudinal section of the copper-niobium composite plate prepared in this embodiment. Figure 3 It can be seen that the inner core wire of the copper-niobium composite strip has a strong texture orientation.

[0044] Figure 4 This is the SEM image of the copper-niobium nanowire core in the copper-niobium composite strip prepared in this example. Figure 4 It can be seen that the copper and niobium core wire composite structure of the bundled structure in the copper-niobium composite plate and strip is complete and continuous.

[0045] Figure 5 TEM images of the nano niobium core wires in the copper-niobium composite strip prepared in this embodiment, wherein Figure (a) is a morphology image of the niobium core wires after corrosion of the copper-niobium composite strip, Figure (b) is a morphology image of a single niobium core wire. Through measurement, its thickness is about 96.43nm, and Figure (c) is a morphology image of a single niobium core wire. It can be seen that there is an amorphous layer with a thickness of 5nm to 10nm at the interface between the niobium core wire and the copper core wire. This low-energy interface layer structure plays an important role in the high-temperature thermal stability of the copper-niobium strip.

[0046] Figure 6 The NS curve of the bending fatigue test of the copper-niobium composite strip prepared in this embodiment is obtained according to the data in Table 2. Figure 6It can be seen intuitively from Table 2 that the copper-niobium composite strip prepared in this embodiment can withstand a large number of cyclic bending circles, indicating that the copper-niobium composite strip prepared in the present invention has very excellent fatigue performance.

[0047] Example 2

[0048] This embodiment includes the following steps:

[0049] Step 1: using an automatic foil winding device, alternately stacking high-purity copper foil and high-purity niobium foil with a mass purity of 99.9% and a thickness of 200 μm in a layered distribution according to a volume ratio of 1:1, and winding them on an automatic winding device, and then placing them in a copper alloy sheath with an outer diameter of 100 mm and a wall thickness of 8 mm to obtain a copper-niobium wound foil composite sheath, and then vacuum degassing the copper-niobium wound foil composite sheath, and then electron beam sealing welding at both ends, and hot extrusion deformation at 700° C., so that the interface of the high-purity copper foil and the high-purity niobium foil is solid-state welded, and a copper-niobium composite rod with a diameter of Φ20 mm and a winding structure is obtained, and then the copper-niobium composite rod with a winding structure is subjected to multi-pass cold drawing with a pass deformation rate of 12% and intermediate annealing at 700° C. for 3 hours to obtain a copper-niobium composite wire with a hexagonal cross-section;

[0050] Step 2: 853 copper-niobium composite wires with a hexagonal cross-section obtained in step 1 are used as core wires for bundling and assembly, and are placed in a copper-nickel-tin alloy sheath with an outer diameter of 100 mm to obtain a copper-niobium bundled composite sheath. The two ends of the copper-niobium bundled composite sheath are then vacuum-sealed and hot-extruded at 750°C to solid-weld the outer copper alloy interface of the inner core wire, and the outer copper alloy of the outer sheath is solid-welded with the outer copper alloy interface of the contacting core wire, to obtain a multi-core wire with a diameter of 20 mm. The copper-niobium clustered composite rod with a cluster structure is then subjected to multi-pass cold drawing with a pass deformation rate of 12%, two intermediate annealings at 700°C for 3 hours, and multi-pass cold drawing with a pass deformation rate of 12% to obtain a copper alloy / copper / niobium structure composite round wire with a diameter of φ4.4mm, an outer layer of high-strength and wear-resistant copper alloy covering an inner high-strength, high-elasticity, high-toughness, high thermal stability and fatigue resistance copper-niobium nanocomposite core wire, such as Figure 1 As shown;

[0051] Step 3: The copper alloy / copper / niobium structure composite round wire with a diameter of φ4.4 mm obtained in step 3 is subjected to a heat treatment at 680°C for 2.5 hours, and then subjected to multiple cold rolling deformation, wherein the pass deformation rates of the multiple cold rolling deformation are: 30% when the thickness of the cold rolled strip is 1 mm or more, 17% when the thickness of the cold rolled strip is 0.5 mm or more and less than 1 mm, 10% when the thickness of the cold rolled strip is 0.3 mm or more and less than 0.5 mm, 3% when the thickness of the cold rolled strip is less than 0.3 mm, and the multiple cold rolling deformation is performed. During the deformation process, the diameter size of the copper alloy / copper / niobium structure composite round wire changes to 4.4mm, 3.71mm, 3.5mm, 2.98mm, 2.53mm, 2.21mm, 1.89mm, 1.61mm, 1.32mm, 1.07mm, 0.89mm, 0.71mm, 0.55mm, 0.49mm, 0.44mm, 0.38mm, and 0.35mm, and finally a high-strength, high-elastic, fatigue-resistant, wear-resistant, and thermally stable copper-niobium composite plate with a thickness of 0.35mm is obtained. Figure 2 shown.

[0052] After testing, the tensile strength σb of the copper-niobium composite strip prepared in this embodiment is ≥1000MPa, the elastic yield strength / elastic modulus is above 0.008, and the number of cyclic loading circles N under a stress level of 30% is ≥1.7×10 6 The softening temperature is above 600°C and the electrical conductivity is above 65% IACS.

[0053] Example 3

[0054] This embodiment includes the following steps:

[0055] Step 1: using an automatic foil winding device, alternately stacking high-purity copper foil and high-purity niobium foil with a mass purity of 99.9% and a thickness of 500 μm in a layered distribution according to a volume ratio of 1:1, and winding them on an automatic winding device, and then placing them in a copper alloy sheath with an outer diameter of 120 mm and a wall thickness of 8 mm to obtain a copper-niobium wound foil composite sheath, and then vacuum degassing the copper-niobium wound foil composite sheath, and then electron beam sealing welding at both ends, and hot extrusion deformation at 700° C., so that the interface of the high-purity copper foil and the high-purity niobium foil is solid-state welded, and a copper-niobium composite rod with a diameter of Φ20 mm and a winding structure is obtained, and then the copper-niobium composite rod with a winding structure is subjected to multi-pass cold drawing with a pass deformation rate of 15% and intermediate annealing at 680° C. for 2.5 hours to obtain a copper-niobium composite wire with a hexagonal cross-section;

[0056] Step 2: 853 copper-niobium composite wires with a hexagonal cross-section obtained in step 1 are used as core wires for bundling and assembly, and are placed in a copper-nickel-silicon alloy sheath with an outer diameter of 150 mm to obtain a copper-niobium bundled composite sheath. The two ends of the copper-niobium bundled composite sheath are then vacuum-sealed and hot-extruded at 750° C. to solid-state weld the outer copper alloy interface of the inner core wire, and the outer copper alloy of the outer sheath is solid-state welded with the outer copper alloy interface of the contacting core wire, to obtain a multi-core bundled wire with a diameter of 20 mm. The copper-niobium cluster composite rod with a multi-core cluster structure is then subjected to multi-pass cold drawing with a pass deformation rate of 10%, intermediate annealing at 680°C for 2.5 hours twice, and multi-pass cold drawing with a pass deformation rate of 10%, to obtain a copper alloy / copper / niobium structure composite round wire with a diameter of φ3.5mm, an outer layer of high-strength and wear-resistant copper alloy covering an inner high-strength, high-elasticity, high-toughness, high thermal stability and fatigue resistance copper-niobium nanocomposite core wire, such as Figure 1 As shown;

[0057] Step 3: The copper alloy / copper / niobium structure composite round wire with a diameter of φ3.5 mm obtained in step 3 is subjected to a heat treatment at 650°C for 3 hours, and then subjected to multiple cold rolling deformation. The pass deformation rates of the multiple cold rolling deformation are: 25% when the thickness of the cold rolled object strip is 1 mm or more, 15% when the thickness of the cold rolled object is 0.5 mm or more and less than 1 mm, 5% when the thickness of the cold rolled object is 0.3 mm or more and less than 0.5 mm, 1% when the thickness of the cold rolled object is less than 0.3 mm, and the pass cold rolling deformation is During the process, the diameter sizes of the copper alloy / copper / niobium structure composite round wires are changed to 3.5mm, 2.98mm, 2.53mm, 2.21mm, 1.89mm, 1.61mm, 1.32mm, 1.07mm, 0.89mm, 0.71mm, 0.55mm, 0.49mm, 0.44mm, 0.38mm, 0.35mm, 0.3mm, and 0.25mm, and finally a high-strength, high-elastic, fatigue-resistant, wear-resistant, and thermally stable copper-niobium composite plate with a thickness of 0.25mm is obtained. Figure 2 shown.

[0058] After testing, the tensile strength σb of the copper-niobium composite strip prepared in this embodiment is ≥1000MPa, the yield strength / elastic modulus is above 0.008, and the number of cyclic loading circles N under a stress level of 30% is ≥1.7×10 6 The softening temperature is above 600°C and the electrical conductivity is above 65% IACS.

[0059] Figure 7 The springback analysis comparison diagram of the copper-niobium composite strips prepared in Examples 1 to 3 of the present invention and the beryllium-nickel-copper strips is shown in FIG. Figure 7It can be seen that under the same strain, the copper-niobium composite strip can rebound completely, while the beryllium-nickel-copper strip undergoes partial permanent plastic deformation. By comparison, it can be seen that the copper-niobium composite strip of the present invention has better resilience.

[0060] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a high-strength, high-elastic, fatigue-resistant copper-niobium composite strip, characterized in that: The method comprises the following steps: Step 1: using an automatic foil winding device to alternately wind a micron-level high-purity copper foil and a high-purity niobium foil in a layered distribution according to a volume ratio of 1:1, and then placing them in a copper alloy sheath to obtain a copper-niobium wound foil composite sheath, and then vacuum-sealing and welding the two ends of the copper-niobium wound foil composite sheath and then performing hot extrusion deformation to make the interface of the high-purity copper foil and the high-purity niobium foil solid-state welded to obtain a copper-niobium composite rod with a winding structure, and then performing multiple cold drawing and intermediate annealing on the copper-niobium composite rod with a winding structure to obtain a copper-niobium composite wire with a hexagonal cross-section; Step 2: The copper-niobium composite wire with a hexagonal cross-section obtained in step 1 is used as a core wire for bundling and assembly and placed in a copper alloy sheath to obtain a copper-niobium bundled composite sheath, and then the two ends of the copper-niobium bundled composite sheath are vacuum-sealed and then hot-extruded to deform, so that the outer copper alloy interface of the inner core wire is solid-state welded, and the outer sheath copper alloy is solid-state welded with the outer copper alloy interface of the contacting core wire, so as to obtain a copper-niobium bundled composite rod with a multi-core bundled structure, and then the copper-niobium bundled composite rod with a multi-core bundled structure is subjected to multi-pass cold drawing, two intermediate annealings, and multi-pass cold drawing to obtain a copper alloy / copper / niobium structure composite round wire with an outer copper alloy layer and an inner copper-niobium core wire; Step 3: heat-treating the copper alloy / copper / niobium structure composite round wire obtained in step 3, and then performing multiple cold rolling deformation to obtain a high-strength, high-elastic, fatigue-resistant, wear-resistant, and thermally stable copper-niobium composite strip; the copper-niobium composite strip has a tensile strength σb ≥ 1000 MPa, a yield strength / elastic modulus of 0.008 or more, and a cyclic loading number N ≥ 1.7×10 6 The softening temperature is above 600°C and the electrical conductivity is above 65% IACS.

2. The method for preparing a high-strength, high-elastic, fatigue-resistant copper-niobium composite strip according to claim 1, characterized in that: The mass purity of the high-purity copper foil and the high-purity niobium foil in step 1 are both 99.9%, and the thickness is the same, both in the range of 150 μm to 500 μm, and the outer diameter of the copper alloy sheath is 80 mm to 120 mm.

3. The method for preparing a high-strength, high-elastic, fatigue-resistant copper-niobium composite strip according to claim 1, characterized in that: The deformation rate of the multi-pass cold drawing in step 1 is 10% to 15%, the temperature of the intermediate annealing is 680° C. to 720° C., and the time is 2.5 h to 3 h.

4. The method for preparing a high-strength, high-elastic, fatigue-resistant copper-niobium composite strip according to claim 1, characterized in that: The copper alloy sheath in step 2 is copper-nickel-silicon or copper-nickel-tin alloy, with an outer diameter of 80 mm to 150 mm, and the temperature of the hot extrusion deformation is 700° C. to 750° C.; the deformation rate of the multi-pass cold drawing is 10% to 15%, and the intermediate annealing temperature is 680° C. to 720° C.; the copper alloy / copper / niobium structure composite round wire is a structure in which an outer layer of high-strength and wear-resistant copper alloy is coated with an internal high-strength, high-elasticity, high-toughness, high thermal stability and fatigue-resistant copper-niobium nanocomposite core wire.

5. The method for preparing a high-strength, high-elastic, fatigue-resistant copper-niobium composite strip according to claim 1, characterized in that: The diameter of the copper alloy / copper / niobium structure composite round wire in step 3 is φ3.5mm~φ5.0mm; the temperature of the heat treatment is 650℃~700℃, and the holding time is 2h~3h; the pass deformation rates of the multiple cold rolling deformations are: when the thickness of the cold rolled object strip is 1mm or more, it is 25%~40%, when the thickness of the cold rolled object is 0.5mm or more and less than 1mm, it is 15%~20%, when the thickness of the cold rolled object is 0.3mm or more and less than 0.5mm, it is 5%~15%, when the thickness of the cold rolled object is less than 0.3mm, it is 1%~5%; the thickness of the copper-niobium composite strip is 0.25mm~0.5mm.

Citation Information

Patent Citations

  • Preparation method of CuNb composite pipe for high-field Nb3Sn wire material

    CN101859612A

  • Preparation method of high-strength high-conductivity copper-niobium multi-core composite wire

    CN105869778A

  • Elastic copper-titanium alloy and preparation method thereof

    CN111733372A

  • Preparation method of copper-niobium alloy cast ingot with uniform structure

    CN118406909A

  • MANUFACTURING METHOD OF Nb3Al SUPERCONDUCTING WIRE, AND COMPOUND WIRE MEMBER THEREFOR

    JP2006079993A